Analysis of the surplus value of driving schools in jember regency in 2024 - Jannah, Tutik Waridatul; Sukidin, Sukidin; Sedyati, Retna Ngesti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study aims to analyze the application of the concept of surplus value in driving schools and explore its impact on the quality of education. this research was conducted based on the need to understand how government interventions can overcome the mismatch of measurable improvement in the quality of education. although previous research related to a structured framework but there are still few studies that discuss it. This study examines how driving schools implement the commitment of the Driving School Program (PSP) to achieve surplus value in the form of 5 interventions from the government. The research uses a qualitative descriptive approach, There are 5 driving schools that are used as case studies in providing in-depth insights. Data collection using in-depth interviews, participatory observations, focus group discussions (FGD) and analysis of modified documents. The respondents were 5 principals of the driving schools and the learning committee as the main respondents, the Coaching Supervisor and other teachers from the 5 driving schools, which was carried out from January to December 2024. this research uses descriptive qualitative research. The data was analyzed using identification, classification and interpretation of the data from the research results. The results were obtained that the achievement of surplus value 3 among 5 driving schools in the range of 51 – 75 or the Developing According to Expectations (BSH) criterion means that the understanding, implementation and commitment of the driving schools have been carried out according to the existing schedule/mentoring timeline, have been consistently implemented, but have not been scanned. In addition, this study also contributed to the improvement of teaching and student engagement of the 5 schools that had performance differences with a surplus value of 3.